Keisha's maze mystery - Benson, Lauren; Burr, Dan (Portland, ME : Magic Attic Press, 1997)
Keisha, annoyed that she is going to have to put up with a visit from her stuck-up cousin Niki, learns a lesson about jumping to conclusions without all the facts after she makes a trip to the magic attic.
6.5
3-6
Keywords: Imagination -- Fiction; Cousins -- Fiction; Imagination -- Fiction; Cousins -- Fiction